Impact of solar event in ionization of ionosphere at middle and low latitudes in the Europe-African sector - (:unkn) unknown (My University, 2016)
This work aims to study the regular variations of the ionosphere at middle and low latitudes and the impact of various events on solar ionization. To quantify these changes, we will use GPS networks to measure the Total Electronic Content (TEC) .This work is part of the project ISWI. The study will include a morphological analysis on regular variations in the ionization time of the Quiet Sun (diurnal variation, seasonal and based on the solar cycle) for the treatment of GPS stations in Europe and Africa over the period analyzed (2000 to 2014); variations disturbed ionosphere associated with solar events selected according to a set of criteria; Analysis of the ROTI index to study the ionospheric scintillation generating degradation positioning at low latitudes and especially Africa.The study will continue with the comparison with existing models in order to identify their performance: the NeQuick2 model modeling software profile of the median vertical ,the ionospheric model IONEX / CODG which is a daily mapping TEC in specific spatial and temporal positions and from the post-processing of GPS measurements on a third coverage mondiale.The component of this study will give prospects for a possible anticipation of the impact of specific solar events on the ionosphere, such modeling gradients in magnetically disturbed period and prediction of the presence of ionospheric scintillation event on some ground-satellite paths.
Keywords: African Research